Early blood pressure lowering in patients with intracerebral haemorrhage and prior use of antithrombotic agents: pooled analysis of the INTERACT studies. Issue 12 (13th May 2016) - Song, Lili; Sandset, Else Charlotte; Arima, Hisatomi; Heeley, Emma; Delcourt, Candice; Chen, Guofeng; Yang, Jie; Wu, Guojun; Wang, Xia; Lavados, Pablo M; Huang, Yining; Stapf, Christian; et al.
Abstract : Objective: Antithrombotic agents increase risks of intracerebral haemorrhage (ICH) and associated adverse outcomes. We determined differential effects of early blood pressure (BP) lowering in patients with/without antithrombotic-associated ICH in the Intensive Blood Pressure Reduction in Acute Cerebral Haemorrhage Trials (INTERACT1 and 2). Design: Post hoc pooled analyses of the INTERACT studies—international, multicentre, prospective, open, blinded end point trials of patients with ICH (<6 h) and elevated systolic BP (SBP 150–180 mm Hg) randomly assigned to intensive (target SBP <140 mm Hg) or guideline-based (SBP <180 mm Hg) BP management. Associations of antithrombotic use and (1) death or dependency (modified Rankin scale scores 3–6) were analysed using logistic regression, and (2) of increased haematoma+intraventricular haemorrhage volume (IVH) with/without intraventricular haemorrhage (IVH) over 24 h were estimated in analyses of covariance. Results: In all, 3184 patients were included in these analyses. Antithrombotic-associated ICH (364 patients, 11%) was not associated with a significantly increased risk of death or dependency (OR 1.38, 95% CI 0.93 to 2.04). There was no heterogeneity in the BP-lowering treatment effect on death or dependency. Among 1309 patients who underwent follow-up CT after 24 h, absolute increase in haematoma±IVH volume was larger (5.2/5.0 mL) in those with compared to those without prior antithrombotics (2.2/0.9 mL; p=0.022/0.031). Intensive BP lowering reduced haematoma±IVH growth by 4.7/7.1 mL in patients on antithrombotics versus 1.3/1.4 mL in those without, although these differences did not reach statistical significance (p homogeneity=0.104/0.059). Conclusions: In patients with ICH, prior antithrombotic therapy is associated with greater haematoma growth, which may be reduced by early intensive BP-lowering treatment. Trial registration number: NCT00226096, NCT00716079 .